2022
DOI: 10.1007/s00415-022-11519-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines in multiple sclerosis patients are related to clinical and radiological measures

Abstract: Background An imbalance of adipokines, hormones secreted by white adipose tissue, is suggested to play a role in the immunopathology of multiple sclerosis (MS). In people with MS (PwMS) of the same age, we aimed to determine whether the adipokines adiponectin, leptin, and resistin are associated with MS disease severity. Furthermore, we aimed to investigate whether these adipokines mediate the association between body mass index (BMI) and MS disease severity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…While some studies did not find any significant effect of APN on the risk [14,15] and the clinical course of the disease [16,17], most authors have associated this adipokine with the inflammatory activity and severity of MS [3,[18][19][20][21]. The effects of APN on the activity of the disease were found to be independent of BMI [3,21] and to involve sex-dependent mechanisms [3,19]. Moreover, Bove et al (2016) [22] also observed sex-based differences in the association of BMI with disease severity.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…While some studies did not find any significant effect of APN on the risk [14,15] and the clinical course of the disease [16,17], most authors have associated this adipokine with the inflammatory activity and severity of MS [3,[18][19][20][21]. The effects of APN on the activity of the disease were found to be independent of BMI [3,21] and to involve sex-dependent mechanisms [3,19]. Moreover, Bove et al (2016) [22] also observed sex-based differences in the association of BMI with disease severity.…”
Section: Discussionmentioning
confidence: 94%
“…Reports on the pathophysiological role of APN blood levels in MS are conflicting. While some studies did not find any significant effect of APN on the risk [14,15] and the clinical course of the disease [16,17], most authors have associated this adipokine with the inflammatory activity and severity of MS [3,[18][19][20][21]. The effects of APN on the activity of the disease were found to be independent of BMI [3,21] and to involve sex-dependent mechanisms [3,19].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is worth noting that EVs released by adipocytes stimulate fatty acid oxidation and migration in melanoma cells [ 54 ] and are involved in macrophage activation [ 55 ]. These findings emphasize the importance of monitoring the AT secretome to enhance disease-modifying therapies for conditions such as multiple sclerosis (MS) [ 56 , 57 ] and cancer cachexia [ 21 , 58 ]. Emerging findings revealed that adipose-derived LCN2 participates in several pathophysiological conditions including inflammation [ 21 , 25 , 26 , 31 , 47 ].…”
Section: Discussionmentioning
confidence: 99%